2011
DOI: 10.2208/jscejhe.67.i_1465
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mowing Down Floating-Leaved Plants on Water Body Structure in Lake Suwa

Abstract: Numerous attempts have been conducted in order to recover emergent plants and submerged plants in various lakes. However, floating-leaved plants, which make water quality worse, have been rarely focused. The purpose of this paper is to evaluate the effect of mowing down the floating-leaved plants area partially in Lake Suwa, where floating-leaved plants-dominated state is observed in shallow zone. We measure water temperature, turbidity and water velocity inside and outside of the floating-leaved plants area. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, since 2005, water chestnut (Trapa sp. ), a floating-leaved plant, has dominated in the coastal area in summer, covering nearly 20% of the lake surface [49]. A luxuriant growth of Trapa sp.…”
Section: Discussionmentioning
confidence: 99%
“…However, since 2005, water chestnut (Trapa sp. ), a floating-leaved plant, has dominated in the coastal area in summer, covering nearly 20% of the lake surface [49]. A luxuriant growth of Trapa sp.…”
Section: Discussionmentioning
confidence: 99%
“…Trapa japonica , a common annual floating‐leaved macrophyte, commonly occurs in Asian shallow and eutrophic lakes along the lakeshore from summer to autumn (Yasuda et al, ). T. japonica bed restrict boat navigation (Toyota, Kato, Imai, & Miyabara, ) and induce hypoxia under the leaves (Frodge, Thomas, & Pauley, ; Hummel & Findlay, ; Yamanaka, ). In Lake Suwa, Japan, T. japonica beds coverage reaches approximately 20% of the lake surface (Toyota et al, ) and results in a large amount of biomass (~500 t in the entire lake, Takei Kaoru, personal communication, November 29, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…T. japonica bed restrict boat navigation (Toyota, Kato, Imai, & Miyabara, ) and induce hypoxia under the leaves (Frodge, Thomas, & Pauley, ; Hummel & Findlay, ; Yamanaka, ). In Lake Suwa, Japan, T. japonica beds coverage reaches approximately 20% of the lake surface (Toyota et al, ) and results in a large amount of biomass (~500 t in the entire lake, Takei Kaoru, personal communication, November 29, 2009). Rahman, Mosaddik, Wahed, and Haque () demonstrated that Trapa bispinosa extracts exert antimicrobial activity against Gram‐positive bacteria.…”
Section: Introductionmentioning
confidence: 99%